BUSINESS TO BUSINESS ARTA BOGA CEMERLANG DI SEMARANG (Information Technology and Telematics, 2015)
Abstract : Arta Boga Shining is one of the distributors are located in the city of Semarang Arta Boga Shining itself was established in 1985 and is the sole distributor of "Parents" who distributes products from a number of manufacturers to all regions in Indonesia. However, the forerunner of Arta Boga Shining as a distribution company has started since 1948. The purpose of this study is to describe a sales system that runs and designing B2B in Arta Boga Shining in Semarang. Web-based information system created with the PHP programming language and MySQL database. There are seven tables in the database to accommodate this system berjalanya process, namely: employee table, table company, group table, the product table, the table entry and exit tables.   Keywords: B2B, ABC Semarang, e-commerce